INFLUENCE OF NITROGEN SUPPLY ON THE ACCUMULATION OF BIOMASS AND LIPOPHILIC COMPOUNDS ACUTODESMUS DIMORPHUS (TURPIN) TSARENKO - Чебан, Лариса (Biological systems, 2022)
The work is devoted to the study of the influence of nitrogen supply on the accumulation of lipophilic compounds of Acutodesmus dimorphus (Turpin) Tsarenko. Acutodesmus dimorphus (Turpin) Tsarenko is a species of green algae of the Scenedesmaceae family. These are cynobial freshwater algae, which are representatives of water bodies of moderate latitudes. Nitrate supply is a key factor in the algae cultivation process. The conjugation of cellular processes of algae will depend on the amount of nitrogen in the nutrient medium. Nitrogen content is the dominant factor in the accumulation of lipophilic compounds in algae biomass. The effect of nitrate supply on the accumulation of biomass, the amount of proteins, lipids and carotenoids of A. dimorphus was determined. To simulate nitrogen deprivation, Yanovsky's medium with a reduced NaNO3 content was used. Janovsky's control medium contained 80 mg/L NaNO3 (100% nitrogen supply). In experimental versions of the environment, the amount of NaNO3 was reduced to 75%, 50% and 25%, respectively. A decrease in available nitrogen in the nutrient medium for A. dimorphus leads to an increase in the amount of triacylglycerols in algae cells. The highest indicator of the number of neutral lipids was noted at 50% and 25% nitrogen supply of A. dimorphus culture. Under conditions of nitrogen starvation, a decrease in the amount of total protein in A. dimorphus cells was noted, but this trend is not directly related to an increase in the amount of triacylglycerols. In order to obtain lipophilic compounds of A. dimorphus, it is recommended to use Yanovsky's medium with 25% NaNO3 content. Under these conditions, we obtain A. dimorphus biomass with an optimal content of triacylglycerols, carotenoids and protein.
Keywords: green algae; lipids; carotenoids; nitrogen supply